Productivity growth in agriculture : an international perspective - Ball, V. Eldon; Fuglie, Keith Owen; Wang, Sun Ling (CABI, 2012)
Increasing food prices have renewed concerns about long-run agricultural demand and supply in the global economy. This book looks at results, methods, and data on international agricultural productivity for a better understanding of long-run trends and he policies that determine them. By presenting an international assessment of total factor productivity growth in agriculture, including up-to-date empirical analysis for developed and developing countries and regions, it provides a response to the rising global scarcity of agricultural production. Essential reading for researchers, policy makers and students.